Use of remote control in the intraoperative telemetry of cochlear implant: multicentric study - Tanamati,Liege Franzini (2019)
Abstract Introduction: The conventional evaluation of neural telemetry and impedance requires the use of the computer coupled to an interface, with software that provides visualization of the stimulus and response. Recently, a remote control (CR220®) was launched in the market, that allows the performance of intraoperative tests with minimal instrumentation. Objective: To evaluate the agreement of the impedance values and neural telemetry thresholds, and the time of performance in the conventional procedure and by the remote control. Methods: Multicentric prospective cross-sectional study. Intraoperative evaluations of cochlear implants compatible with the use of CR220® were included. The tests were carried out in the 22 electrodes to compare the time of performance in the two situations. The agreement of the neural telemetry threshold values obtained from five electrodes was analyzed, and the agreement of impedance was evaluated by the number of electrodes with altered values in each procedure. Results: There were no significant difference between the impedance values. There was a moderate to strong correlation between the electrically-evoked compound action potential thresholds. The mean time to perform the procedures using the CR220 was significantly lower than that with the conventional procedure. Conclusion: The use of the CR220 provided successful records for impedance telemetry and automatic neural response telemetry.